Analysis and experiment of deformation and draping characteristics in hemisphere preforming for plain woven fabrics. (July 2021) - Mei, Ming; He, Yujia; Yang, Xujing; Wei, Kai
Abstract: Currently, the analytical analysis cannot describe the deformation and draping behavior during hemisphere preforming using plain woven fabrics, especially considering the fabric deformation outside the hemisphere and the effect of processing parameters. Thus, an analytical analysis was established to characterize the sliding and shearing behavior for a typical hemisphere preforming for the plain woven fabric. The experiments were conducted, and the root mean square values for the sliding and shearing between the analytical and experimental results are small, demonstrating the effectiveness of the analytical analysis. With the reduction of the corner radius of the die and the gap between the punch and die, the sliding ratio is larger than 1.0, indicating an increase in yarn sliding . In addition, the shearing deformation in the quasi tensile region is still generated and reaches a maximum value of 4.5° both in analytical prediction and in experimental measurements. Moreover, the analytical analysis is capable of characterizing the draping degree, which is shown to increase non-linearly with increasing punch depth. The reduction of the gap and corner radius enlarges the draped region, improving the draping degree. This work demonstrates that an analytical analysis can be used to gain an insight into the deformation and draping mechanisms of plain woven fabrics.